Forms Of Money Laundering Crimes In The Perspective Of The Money Laundering Crime Law In Indonesia - Andre Yosua M; Muhammad Gastari (International Journal of Social Welfare and Family Law, 2024)
Today's crimes are increasingly showing increasingly modern patterns, one of which is the crime of money laundering (" money laundering "). The crime of money laundering is understood as the act of hiding the origin of funds which are illegal because they are obtained from a criminal act which appears to be legitimate. Law Number 8 of 2010 concerning Prevention and Eradication of Money Laundering. The stages of money laundering which consist of conversion (" placement "), layering (" layering "), and integration ("integration") in its development are carried out by utilizing cyberspace (" cyber "), so that it constitutes " cyber crime ", the handling of which is increasingly difficult and complex, because this crime can be a transnational crime, even though law enforcement officers in carrying out their authority are limited by jurisdiction. Apart from that, special competence and expertise is also needed in the field of " cyber ". " Cyber money laundering " is an inevitability that must be faced as a form of " white collar crime " in the 21st century era, so that efforts to prevent and eradicate the crime of money laundering can be achieved. implemented optimally.